Dampak Pandemi Covid-19 terhadap Kunjungan Objek Wisata Pantai Siuri Desa Toinasa Kabupaten Poso - Balimawo, Renilda Wiliandini; Sumilat, Grystin Djein; Ramadhan, Muhamad Isa (GEOGRAPHIA : Jurnal Pendidikan dan Penelitian Geografi, 2024)
The Covid-19 pandemic has significantly impacted the management of Pantai Siuri in Toinasa Village, Poso Regency. This research employs a qualitative method, utilizing data collection through observation, interviews, and documentation to analyze the effects on visitor numbers, tourism management, and the role of the government. The study reveals a decrease in income and reservation cancellations due to the Covid-19 pandemic, along with the obligation for tourists to adhere to health protocols. Despite facing losses, the management still keeps the tourist site open to meet daily needs. The government implements health protocols for the safety of tourists, while the village government focuses on cleanliness, beauty, and pollution prevention.